Consolidating Indonesia’s Fragile Elections Through E-Voting: Lessons Learned from India and the Philippines - Elven, Tareq Muhammad Aziz; Al-Muqorrobin, Shalahuddin Ahmad (Universitas Muhammadiyah Yogyakarta, 2020)
This research argues that implementing the electronic voting (e-voting) system in Indonesia is urged following the nation's first-ever 2019 simultaneous elections, which cost a deadly price of 527 election official lives of reported extreme fatigue during and after the event. Billed as